Phenylephrine impairs host defence mechanisms to infection: a combined laboratory study in mice and translational human study. (March 2021) - Stolk, Roeland F.; Naumann, Flavia; van der Pasch, Eva; Schouwstra, Joost; Bressers, Steffi; van Herwaarden, Antonius E.; Gerretsen, Jelle; Schambergen, Roel; Ruth, Mike; van der Hoeven, Hans G.; van Leeuwen, Henk J.; Pickkers, Peter; et al.
Abstract: Background: Immunosuppression after surgery is associated with postoperative complications, mediated in part by catecholamines that exert anti-inflammatory effects via the β-adrenergic receptor. Phenylephrine, generally regarded as a selective α-adrenergic agonist, is frequently used to treat perioperative hypotension. However, phenylephrine may impair host defence through β-adrenergic affinity. Methods: Human leukocytes were stimulated with lipopolysaccharide (LPS) in the presence or absence of phenylephrine and α- and β-adrenergic antagonists. C57BL/6J male mice received continuous infusion of phenylephrine (30–50 μg kg −1 min −1 i.v.) or saline via micro-osmotic pumps, before LPS administration (5 mg kg-1 i.v.) or caecal ligation and puncture (CLP). Twenty healthy males were randomised to a 5 h infusion of phenylephrine (0.5 μg kg −1 min −1 ) or saline before receiving LPS (2 ng kg −1 i.v.). Results: In vitro, phenylephrine enhanced LPS-induced production of the anti-inflammatory cytokine interleukin (IL)-10 (maximum augmentation of 93%) while attenuating the release of pro-inflammatory mediators . These effects were reversed by pre-incubation with β-antagonists, but not α-antagonists. Plasma IL-10 levels were higher in LPS-challenged mice infused with phenylephrine, whereas pro-inflammatory mediators were reduced. Phenylephrine infusion increased bacterial counts after CLP in peritoneal fluid (+42%, P =0.0069), spleen (+59%, P =0.04), and liver (+35%, P =0.09). In healthy volunteers, phenylephrine enhanced the LPS-induced IL-10 response (+76%, P =0.0008) while attenuating plasma concentrations of pro-inflammatory mediators including IL-8 (–15%, P =0.03). Conclusions: Phenylephrine exerts potent anti-inflammatory effects, possibly involving the β-adrenoreceptor. Phenylephrine promotes bacterial outgrowth after surgical peritonitis. Phenylephrine may therefore compromise host defence in surgical patients and increase susceptibility towards infection. Clinical trial registration: NCT02675868 (Clinicaltrials.gov).